2021
DOI: 10.1097/md.0000000000025639
|View full text |Cite
|
Sign up to set email alerts
|

The safety and effectiveness of salvianolate in preventing perioperative venous thromboembolism in China

Abstract: Background: Salvianolate, a common drug for stabilizing heart disease and Angina Pectoris, is considered to be off-label for preventing venous thromboembolism (VTE) or anticoagulation at present. However, many clinical studies have showed that salvianolate can effectively inhibit the deep-vein thrombosis (DVT) incidence, and prevent VTE of perioperative patients in the real world in China. Objective: This analysis aimed to evaluate the effectiveness and safety of salvia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…10,12 It is safe to prevent DVT during perioperative period without bleeding tendency and widely used in perioperative period in China. 15,17 Salvianolate is mainly composed of salvianolic acid B, which can inhibit the oxidation modification of low density lipoprotein, regulate blood lipids, reduce blood viscosity, enhance fibrinolytic activity, inhibit erythrocyte aggregation to improve high coagulation state and prevent thrombosis. [10][11][12]15,17 In this study, the incidence of DVT in salvianolate group was significantly lower than that in enoxaparin group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10,12 It is safe to prevent DVT during perioperative period without bleeding tendency and widely used in perioperative period in China. 15,17 Salvianolate is mainly composed of salvianolic acid B, which can inhibit the oxidation modification of low density lipoprotein, regulate blood lipids, reduce blood viscosity, enhance fibrinolytic activity, inhibit erythrocyte aggregation to improve high coagulation state and prevent thrombosis. [10][11][12]15,17 In this study, the incidence of DVT in salvianolate group was significantly lower than that in enoxaparin group.…”
Section: Discussionmentioning
confidence: 99%
“…15,17 Salvianolate is mainly composed of salvianolic acid B, which can inhibit the oxidation modification of low density lipoprotein, regulate blood lipids, reduce blood viscosity, enhance fibrinolytic activity, inhibit erythrocyte aggregation to improve high coagulation state and prevent thrombosis. [10][11][12]15,17 In this study, the incidence of DVT in salvianolate group was significantly lower than that in enoxaparin group. Although the changing trends of indexes in the two groups were roughly the same, the indexes…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, salvianolate injection has been used for coronary heart disease treatment in the clinic for more than 15 years in China. It has been used in clinical practice for the treatment and prevention of cardio-cerebral vascular diseases, and its safety profile is well established in China (Chen et al, 2016;Zhang et al, 2016;Dong et al, 2018;NanZhu et al, 2018;Shen et al, 2020;Chai et al, 2021). Our previous study showed that salvianolate attenuated osteogenic inhibition and suppressed hyperactive bone resorption, which lead to the recovery of bone mass and bone mechanical properties in prednisone-treated lupus mice (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%